Integrasi Evaluasi Kesesuaian Lahan dan Pengelolaan Lahan Lokal Bawang Merah di Kecamatan Larangan, Kabupaten Brebes: Aplikasi Pendekatan Ilmu Pertanian Terapan - Valdya Hartati Lestari; Dyah Tjahyandari Suryaningtyas; Sri Mulatsih (Postgraduate, University of Mataram, 2025)
Larangan District as one of the centers of shallot production with the highest potential in Brebes Regency, Indonesia shows that the intensive land management system practiced by local farmers with excessive agrochemical inputs has caused negative environmental impacts and a decline in shallot production. This study aims to integrate agricultural land suitability evaluation with local land management of shallot, through the agricultural science technology approach for increase productivity of shallot and preserving local land management. The research methods include soil sampling, laboratory analysis, spatial data analysis using the matching and overlay method employing Inverse Distance Weighting Interpolation (IDW), as well as an social data analysis with ethnographic approach through in-depth interviews and participatory observation, and also descriptive analysis. The results shows that the actual land suitability of shallot are 2,564.95 ha as S2 class with limiting factors of rainfall, root medium, nutrient retention, and available nutrients, 7,140.05 ha as S3 class and 6,284.99 ha as N class with limiting factor of rainfall. The integration of agricultural science technology with local land management practices, such as gilir giring water management and mupuk organic fertilization, offers a sustainable pathway to address limiting factors with implementation of GIS-based zoning programs combined with farmer field schools for knowledge transfer that synthesizes scientific innovation, without compromising local farming community.